Determination of Bivalves and Gastropods Found on Binasi Beach, Sorkam, Central Tapanuli - Felix Situngkir; Delianis Pringgenies; Sri Sedjati (Jurnal Moluska Indonesia, 2022)
Mollusks are the second largest invertebrate with a number of species reaching 50.000.  Mollusks have a soft body, some classes are covered with shells as a form of self-defense. Mollusks play an important role in ecosystems, where mollusks can be used as aquatic bioindicators. Gastropods and Bivalves are the largest class of Mollusks. Gastropods or snails, have a conical shell shape. Lives in subtidal waters that have muddy substrate. Bivalves or clams have two pieces of shell to protect their soft body, live in intertidal areas with sandy substrates. Binasi Beach is a tourist beach that has a white sand. The goal of this study was to determine the types of bivalve and gastropod found in Binasi Beach. The method used is descriptive analysis where the analysis is carried out according to the description in the field. The results of the analysis showed that two species of mollusks were found, they are Donax deltoides from the Bivalvia class and Turritella terebra from the Gastropod class. Donax deltoides has a convex symmetrical shell where the posterior is shorter than the anterior. The Umbo is not very prominent but can still be seen clearly. Donax deltoides was found 166 tails with a dominant shell length of 26-30 mm by 43.4%. Turriterlla terebra has a conical shell shape. Apex is the shell with the oldest age. Turritella terebra found 4 tails where the largest shell size has a length of 96 mm and a diameter of 18 mm.